Immunohistochemical study of Ito cells of spontaneous cholangiohepatitis in broiler chickens - Handharyani, E; Ochiai, K.; Winarsih, W.; Harlina, E.; Estuninngsih, S. (Indonesian Journal of Animal and Veterinary Sciences, 2001)
The function of Ito cells is expanding from a fat-storing site to a center of extracellular matrix metabolism and mediator production in the liver. Immunohistochemical reactivities of Ito cells were examined in eight livers of broiler chickens affected with spontaneous cholangiohepatitis and six chicken livers with malformation of extrahepatic biliary tracts. The livers in both groups revealed severe diffuse fibrosis. Ito cells expressing HHF35 muscle actin and desmin actively proliferated in the fibrotic foci of the all livers. The immunoreactivities of Ito cells to antibodies were enhanced compared with those in normal livers. There were no immunohistochemical differences between the Ito cells of two groups. From these findings, it was suggested that Ito cells actively proliferate and show enhanced immunoreactivities in the livers affected with cholangiohepatitis and malformation of extrahepatic biliary tracts.Key words: Cholangiohepatitis, immunohistochemistry, ito cell. broiler chicken